1995
DOI: 10.1063/1.871273
|View full text |Cite
|
Sign up to set email alerts
|

A general critique of inertial-electrostatic confinement fusion systems

Abstract: The suitability of various implementations of inertial-electrostatic confinement (IEC) systems'for use as D-T, D-D, D-3 He, p-l 1 B, and p-6 Li reactors is examined; these IEC designs create a deep electrostatic potential well within the plasma in order to confine and accelerate ions, and they typically use magnetic fields or electrostatic grids to confine electrons. It is shown that while an IEC reactor would have the advantages of high power densities and relatively simple engineering design when compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…These collisions add angular momentum to the particles and cause the desired focus to expand. Consequently, either the energy cost of maintaining the beamlike ion distribution exceeds the fusion energy gain 9,10 or the fusion power density becomes too small as the ion focus spreads.…”
Section: Introductionmentioning
confidence: 99%
“…These collisions add angular momentum to the particles and cause the desired focus to expand. Consequently, either the energy cost of maintaining the beamlike ion distribution exceeds the fusion energy gain 9,10 or the fusion power density becomes too small as the ion focus spreads.…”
Section: Introductionmentioning
confidence: 99%
“…Nevins 11 and Rider 12 predict that thermalization of ion flows through core collisions would lead to the collapse of the convergence in an idealized highly recycling central ion flow. Although the gridded experiments studied to date find a steady flow convergence, the particles are removed at a rate faster than the thermalization rate ͑i.e., via grid or charge-exchange collisions, see Sec.…”
Section: Introductionmentioning
confidence: 99%
“…10 While these gridless devices have more promise for higher reactivity, recent theoretical appraisals of such systems, which more extensively account for thermalizing collisional effects and the overall power balance, determine that a power production scheme is not possible based on these types of devices without circumventing these basic issues. 11,12 Despite the differences in the origin of the confining electrostatic fields, a common figure of merit for all proposed a͒ Electronic mail: thorson@uwmfe.neep.wisc.edu SCIF approaches is the attainable degree of focusing of the ion flow at the center. This is known as the flow convergence, and it is a critical parameter for all high-reactivity designs which rely on the counter-streaming ion flows providing the system reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies using simple analytic models have indicated that such systems cannot scale to net energy producing devices. 11,12 However, these studies have several approximations, and a more complete study using a bounce averaged Fokker-Planck model indicated that if the ion distributions are close enough to thermal, net energy gains are possible, although the fusion power densities are small. 13 The underlying problem is that for nonthermal systems, the Coulomb scattering cross sections are larger than the fusion cross sections.…”
Section: Introductionmentioning
confidence: 99%